Automatic extraction of composite terms for construction of ontologies: an experiment in the health care area - DOI: 10.3395/reciis.v3i1.244en - Lucelene Lopes; Renata Vieira; Maria José Finatto; Daniel Martins; Adriano Zanette; Luiz Carlos Ribeiro Jr (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2009)
In this article we demonstrate the use of the tool OntoLP in the ontology construction process in an experiment in the health care area. Specifically, terms based on a corpus in the pediatrics area are extracted. We compare the result obtained by the tool with the reference results of a list of terms obtained manually. In this comparison, bigrams and trigrams obtained through different methods are analyzed. We conclude the work by observing the advantages of processing by including complex linguistic information such as syntactical and semantic analysis.